The Effect of Pediatric Massage Therapy on Constipation in Formula-Fed Infants (6-12 months) - Herlina Listyaningrum; Oon Fatonah Akbarini; Rini Sulistiawati; Rakhmawati (Poltekkes Kemenkes Palu, 2026)
Background: Constipation is a prevalent health problem in infants. It is a condition in which infants have difficulty defecating, bowel movements ≤ 3 times a week, and hard and large feces. In Indonesia, the prevalence of constipation in infants is 15.7%, and it needs to be treated appropriately. The effects of constipation are classified into two categories: short-term and long-term. Short-term effects can manifest as discomfort in infants, anorexia, and lack of weight gain. Non-pharmacological interventions, such as pediatric massage therapy, are effective management strategies for infant constipation. Methods: This study employed a one-group pretest-posttest quasi-experimental design with 38 formula-fed constipation infants aged 6-12 months. The pediatric massage therapy intervention, three times a week, was assessed before and after using the Bristol Stool Chart questionnaire. Results: Based on the statistical analysis of 38 respondents (n = 38), a Z value of −5.42 was obtained with a p value (ρ) = 0.000. This result indicates a highly significant statistical difference/relationship (p < 0.05), so the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted. Conclusion: Pediatric massage therapy is an effective complementary therapy for managing constipation in formula-fed infants aged 6-12 months at the Puskesmas Sungai Besar, Ketapang Regency